Artificial intelligence seen through the lens of bateson’s ecology of mind - Griffiths, Dai (Universidad Internacional de la Rioja, 2022)
Gregory Bateson developed a number of ideas which are relevant to artificial intelligence, and in particular to the ascription of qualities such as mind, consciousness, spirituality and the sacred. Relevant sections of Bateson’s key works are discussed, and his intellectual framework for an ecology of mind is summarized, and in particular his concepts of mind, learning, and the sacred. These are then applied to discuss whether artificial intelligence applications can be considered to possess ‘mind’. It is concluded that symbolic artificial intelligence falls short of Bateson’s criteria for mind, as do neural networks, although approach more closely. Nor are computers based on the rules of formal logic able to engage with the sacred, which is paradoxical in nature. However, artificial intelligence applications can form part of an ecology of mind and can be involved in the experience of the sacred. Bateson’s writing remains a fertile source of ideas relevant to an understanding of the nature and capabilities of artificial intelligence.
Keywords: artificial neural networks; bateson; mind; sacred; symbolic artificial intelligence; Scopus; JCR